Moving up the Residential Hierarchy: A New Remedy for an Old Injury Arising from Housing Discrimination - Kathleen C. Engel (Washington University Law Quarterly, 1999)
In this Article, I demonstrate that claims for lost access to desirable communities can be easily incorporated into an extant category of compensable injuries under the Fair Housing Act. I then introduce a method for assessing the value of this injury. In brief, the method compares the price of housing that a victim of discrimination obtained to the price of the housing he sought and was unlawfully denied to approximate the value of living in the more desirable community. The virtue of the method is that it provides adjudicators with a concrete basis for calculating damages for lost access to a desirable community. In the first part of the Article, I discuss the extent of housing discrimination in the United States, the role discrimination plays in limiting people’s access to the bundle of goods and services that desirable communities provide, the fair housing laws, current remedies under the laws, and the failure of the laws to provide a remedy to people who are denied access to desirable communities as a result of discrimination. In Part II, I describe the method for calculating damages for lost access to a desirable community and discuss some of its complexities. In Part III, I discuss the potential impact of these new damage calculations on the fair housing enforcement scheme.
Keywords: Race discrimination in housing; Valuation; Compensatory damages; Remedies (Law); Fair Housing Act of 1968